A COMPARISON BETWEEN THE VIEWS OF TURAS FIQH AND NEW FIQH REGARDING JARIMAH HUDUD PENALTIES: ISLAMIC LAW AND LANGUAGE REVIEW - Hannani (Al-Risalah, 2021)
There is a difference of opinion between salaf scholars and modern scholars regarding the implementation of hudud jarimah. Some of them try to maintain their understanding according to the text, they want the implementation of jarimah hudud to be adapted to the practices that occurred at the time of the Prophet. While others want a new interpretation regarding jarimah hudud. Therefore, in this article the researcher wants to explain the views of salaf scholars and modern scholars regarding jarimah hudud and how linguistic interpretation relates to jarimah hudud. The method used in this study is the comparative method, by comparing the opinions of salaf scholars and modern scholars regarding jarimah hudÅ«d. This research is a library research by collecting the opinions of scholars from various books and using descriptive analysis methods. The results of this study concluded that according to salaf scholars, jarimah hudud punishment is something that is ta'abbudi in nature which does not accept qiyas and ta'lil. their language interpretation also follows the maqshadi of sahabah and scholars which includes the terms of the crime and the conditions of the offender. While modern scholars try to reinterpret the maqashid uqubah and expand the arena of hudud and its interpretation.